1990
DOI: 10.1038/sj.bdj.4807231
|View full text |Cite
|
Sign up to set email alerts
|

Enamel defects in the primary dentition of children born weighing less than 2000 g

Abstract: The findings for enamel defects in the primary dentition of a group of low birthweight (LBW) children were related to their perinatal medical histories. Examination of 110 LBW children and 93 control children aged 5 years showed that significantly more of the LBW children (71%) had hypoplasia than controls (15%), but there was no difference in opacities alone (LBW 25%, control 26%). In the LBW group, defects were seen more often in children classified as ill during the perinatal period, who received ventilator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
55
1
12

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 0 publications
7
55
1
12
Order By: Relevance
“…34 Such defects will be chronologically laid down in the teeth depending on the state of development at the time of interference, the effect is directly related to the degree of systemic upset. There may be pitting or grooving which predisposes to extrinsic staining of the enamel in the region of tooth disturbed, often then becoming internalised (Fig.…”
Section: Enamel Hypoplasiamentioning
confidence: 99%
“…34 Such defects will be chronologically laid down in the teeth depending on the state of development at the time of interference, the effect is directly related to the degree of systemic upset. There may be pitting or grooving which predisposes to extrinsic staining of the enamel in the region of tooth disturbed, often then becoming internalised (Fig.…”
Section: Enamel Hypoplasiamentioning
confidence: 99%
“…The present results concerning the RBD agree with those reported by other investigators (6,(21)(22)(23) who reported that malnutrition can cause a rise in the prevalence of caries. Various factors may have contributed to the high prevalence of caries found with the use of the RBD, such as enamel malformation due to episodes of malnutrition (24)(25)(26)(27)(28)(29), affected salivary glands (17,23,30,31), and the composition of the diet itself which, in addition to being deficient in proteins, vitamins and minerals, is rich in carbohydrates (10). When comparing the results for different times of animal feeding, we observed that the animals fed 30 days (1A and 2A) presented caries with less prevalence than the animals fed 60 days (1B, 2B), except for groups 3A and 3B.…”
Section: Resultsmentioning
confidence: 99%
“…Esse padrão de cárie desenvolve-se muito rapidamente em pré-escolares, afetando as superfícies dos dentes que são naturalmente livres de cárie 2,3 . Considerando que a doença é influenciada pelo contexto social, essa discussão vai além dos limites das questões de saúde bucal e adentra os limites da equidade social 4 . Fatores de risco perinatais podem resultar em condições de saúde bucal desfavoráveis, considerando que crianças com baixo peso ao nascer tendem a desenvolver defeitos de esmalte, o que facilita a adesão e colonização de bactérias cariogênicas.…”
Section: Introductionunclassified